Correction: Synthesis of midblock-quaternized triblock copolystyrenes as highly conductive and alkaline-stable anion-exchange membranes. Issue 14 (23rd March 2017) - Zhu, Meng; Zhang, Min; Chen, Quan; Su, Yanxia; Zhang, Zhijie; Liu, Lei; Wang, Yiguang; An, Linan; Li, Nanwen
Abstract : Correction for 'Synthesis of midblock-quaternized triblock copolystyrenes as highly conductive and alkaline-stable anion-exchange membranes' by Meng Zhu et al., Polym. Chem., 2017, DOI: 10.1039/c6py02213h.